Ovarian stimulation in poor responders for ART - Strowitzki, Thomas (Reproduktionsmedizin, 1999)
The poor ovarian response, i. e. an inadequate follicular development after gonadotrophin treatment, is still a challenge. A poor response is defined by a maximum of 3 follicles and an estradiol level <500 pg/ml. A further increment above a dose of 450 IU daily did not improve the ovarian response. In contrast a reduction of GnRH analogues combined with an estrogen preloading by contraceptive pills showed promising results. The supplementation of the stimulation cycle with growth hormone was under debate in the early 1990s and should not further be used. Furthermore, corticoids did not influence the ovarian response positively. Since most poor responder patients are normocyclic women with sufficient ovulatory cycles, an IVF attempt in a spontaneous cycle can be considered.
Es besteht kein Link zum Volltext des Artikels
Gesehen am 01.12.2020